2020
DOI: 10.1002/nafm.10440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed DC Frequency on Capture Efficiency and Spinal Injury of Trout in Small Streams

Abstract: Electrofishing studies in the 1990s established that higher frequencies of pulsed DC (e.g., 60 Hz) generally result in more spinal injury to fish in comparison with lower pulse frequencies (e.g., 30 Hz). In response to those findings, some agencies adopted low pulse frequency standards to minimize fish injury. However, those earlier studies did not assess whether capture efficiency (CE) was also influenced by pulse frequency. We sampled small trout streams (1–6‐m average width; SE = 0.14 m) by backpack electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Voltage decreases during a PEC discharge, however, so the voltage gradient in the water is probably not sufficient (less than 0.1V cm À1 ) to induce a neuromuscular reaction in fishes. During depletion captures, Chiaramonte et al (2020) found greater capture efficiency when they electrofished salmonids with a PDC-60Hz than a PDC-30Hz. This suggests that frequency can influence results (estimation of abundance and capture efficiency with the continual application of electricity) when using depletion sampling, but not, according the present study, when using sampling points (CPUE with a discrete application of electricity).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Voltage decreases during a PEC discharge, however, so the voltage gradient in the water is probably not sufficient (less than 0.1V cm À1 ) to induce a neuromuscular reaction in fishes. During depletion captures, Chiaramonte et al (2020) found greater capture efficiency when they electrofished salmonids with a PDC-60Hz than a PDC-30Hz. This suggests that frequency can influence results (estimation of abundance and capture efficiency with the continual application of electricity) when using depletion sampling, but not, according the present study, when using sampling points (CPUE with a discrete application of electricity).…”
Section: Discussionmentioning
confidence: 94%
“…Beaumont et al (2000) demonstrated under experimental conditions that PDC captured rainbow trout more efficiently than PEC but that the shape of PDC at a given power had no influence. Moreover, Chiaramonte et al (2020) found a difference in the probability of capturing trout between two PDC frequencies (30 Hz and 60 Hz). Some points still need to be explored, such as the effect of DC on the ability to catch fishes and the relation between higher frequency and injury to fishes.…”
Section: Introductionmentioning
confidence: 98%
“…Scatterplots of peak voltage and peak current over the range of water conductivity in stream reaches in the study by Chiaramonte et al (2020). The inverse relationship between voltage and current occurs because average power is held at or near 100 W regardless of water conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we used a general linear model to evaluate whether ambient conductivity (as a continuous variable) affected average power output; while we already knew that power output differed between habitat types (i.e., between riffles and pools, as was described above), we included habitat type (as a discrete variable) in the model, as well as a conductivity × habitat interaction term in order to evaluate whether the difference in power output between riffles and pools was affected by changes in conductivity. Finally, we used a general linear model to evaluate whether average power output affected CE; while we already knew (from Chiaramonte et al 2020) that pulse frequency affected CE, we included pulse frequency (as a discrete variable) in the model, as well as a pulse frequency × power output interaction term in order to determine whether the difference in CE between pulse frequencies was affected by changes in power output. To obtain a single power value for each reach to relate to CE, we used the mean of the four average power output values (pool and riffle, start and finish).…”
Section: Methodsmentioning
confidence: 99%
“…Although other habitat features may affect detection probability of stream fishes (e.g., substrate size proportion, instream habitat complexity, and water clarity; Meyer and High 2011; Lamothe et al 2019), we focused on electrofishing effort because we expected that detection probability of both Brook Trout and Brown Trout would increase with sampling effort. Additionally, detection probability has been estimated to be high for trout in wadeable streams Kanno et al 2015;Chiaramonte et al 2020). After comparing detection model results, we used estimated overall detection probabilities to develop a cumulative detection curve for each species to determine how additional sampling occasions (i.e.…”
Section: Catchment-scale Modelsmentioning
confidence: 99%